Will Phosphate Bio-Solubilization Stimulate Biological Nitrogen Fixation in Grain Legumes? - Janati, Walid; Benmrid, Bouchra; Elhaissoufi, Wissal; Zeroual, Youssef; Nasielski, Joshua; Bargaz, Adnane (Frontiers in Agronomy, 2021)
Biological nitrogen fixation (BNF) refers to a bacterially mediated process by which atmospheric N2 is reduced, either symbiotically or non-symbiotically, into ammonia (NH3) in the presence of the enzyme complex nitrogenase. In N2-fixing grain legumes, BNF is often hampered under low phosphorus (P) availability. Phosphorus plays a vital role in BNF, and the P status of legume, particularly nodules, as well as P availability in the rhizosphere regulate BNF. Besides adequate P fertilization, to ensure nodule functioning, other plant traits (i.e., extensive rooting system and their spatial distribution, hyper-nodulation, root exudates, rhizosphere acidification, and heterogeneity) contribute to greater P uptake and hence BNF. The positive interaction between P availability and BNF can be exploited by beneficial soil P solubilizing microorganisms (PSM). These microorganisms can increase plant-available P by modifying either soil processes in the rhizosphere, or promoting plant traits that lead to increased P uptake by production of plant growth-promoting substances, both of which could indirectly influence the efficiency of BNF in legumes. In this review, we report on the importance of microbial P bio-solubilization as a pathway for improving BNF in grain legumes via PSM and P solubilizing bacteria (PSB). Because BNF in legumes is a P-requiring agro-ecological process, the ability of soil PSB to synergize with the rhizobial strains is likely a key belowground process worth investigating for advanced research aiming to improve rhizosphere biological functions necessary for sustainable legume-base cropping systems.